2015
DOI: 10.1021/acs.biochem.5b00010
|View full text |Cite
|
Sign up to set email alerts
|

Variable Active Site Loop Conformations Accommodate the Binding of Macrocyclic Largazole Analogues to HDAC8

Abstract: The macrocyclic depsipeptide Largazole is a potent inhibitor of metal-dependent histone deacetylases (HDACs), some of which are drug targets for cancer chemotherapy. Indeed, Largazole partially resembles Romidepsin (FK228), a macrocyclic depsipeptide already approved for clinical use. Each inhibitor contains a pendant side chain thiol that coordinates to the active site Zn2+ ion, as observed in the X-ray crystal structure of the HDAC8–Largazole complex [Cole, K. E.; Dowling, D. P.; Boone, M. A.; Phillips, A. J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 44 publications
2
67
0
Order By: Relevance
“…2931,34,44,49 Accordingly, P91 is approximately 27–29 Å away from the active site Zn 2+ ion, depending on the conformation of the L2 loop. With a residual catalytic activity of 86% compared with the wild-type enzyme (Table 1), P91L HDAC8 is the least functionally compromised of the mutants described herein.…”
Section: Resultsmentioning
confidence: 99%
“…2931,34,44,49 Accordingly, P91 is approximately 27–29 Å away from the active site Zn 2+ ion, depending on the conformation of the L2 loop. With a residual catalytic activity of 86% compared with the wild-type enzyme (Table 1), P91L HDAC8 is the least functionally compromised of the mutants described herein.…”
Section: Resultsmentioning
confidence: 99%
“…2330 Indeed, HDAC8 is an excellent model system for understanding catalysis by all metal-dependent HDACs. Based on the crystal structure of an HDAC-like protein from Aquifex aeolicus reported five years prior to the structure determination of HDAC8, a catalytic mechanism was proposed for the metal-dependent HDACs in which tandem histidine residues H142 and H143 serve as a general base-general acid catalyst pair.…”
mentioning
confidence: 99%
“…11,21 For SAHA-inhibitors, the hydroxamate acid moiety chelates the metal ions (Zn 2+ ) in the active site pocket, while the aliphatic chain and the capping moiety interact with the hydrophobic pocket and the protein surface. 22,23 Crystallographic and computational studies have identified that two loops (L1 and L2) located in the vicinity of the active site pocket entrance are highly malleable to effectively adopt and catalyze structurally different substrates.…”
mentioning
confidence: 99%